Internal Investigations in Compliance Matters: What Role for Legal Professional Privilege in Europe? - Kruessmann, Thomas (European business law review, 2021)
Information is key to understanding possible wrongdoing in corporations. When allegations of wrongdoing occur, management often invites external counsel to conduct internal investigations because legal professional privilege is seen as crucial in protecting information. In the post-Brexit EU, the objective scope of such privilege is under debate while there is little alignment with developments in the UK. This paper will explore what the deepening divide in the understanding of legal professional privilege may mean. It proposes a policy model, summarizes recent developments in England and Germany and comes to some refined conclusions to serve a broader comparative analysis of internal investigations.